2015
DOI: 10.1002/pchj.99
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in attention and memory toward emotional stimuli

Abstract: From the perspectives of time perception and motivation, socioemotional selectivity theory (SST) postulates that in comparison with younger adults, older adults tend to prefer positive stimuli and avoid negative stimuli. Currently the cross-cultural consistency of this positivity effect (PE) is still not clear. While empirical evidence for Western populations is accumulating, the validation of the PE in Asians is still rare. The current study compared 28 younger and 24 older Chinese adults in the processing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Fifth, there were age differences between the two samples-participants in Study 1 were somewhat older than those in Study 2. There is some evidence that AB towards unmasked, positive stimuli is impacted in healthy, older adults (e.g., age 60+; Bi and Han, 2015 ; Namaky et al, 2017 ); however, it is unclear how (a) this research applies to middle-aged adults (such as those in Study 1), (b) this might extend to a masked dot-probe paradigm, or (c) the effect of trauma impacts SST. Sixth, the majority (94%) of Study 1 participants had a comorbid Substance Use Disorder (SUD) diagnosis, where only a portion (35%) of Study 2 did.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, there were age differences between the two samples-participants in Study 1 were somewhat older than those in Study 2. There is some evidence that AB towards unmasked, positive stimuli is impacted in healthy, older adults (e.g., age 60+; Bi and Han, 2015 ; Namaky et al, 2017 ); however, it is unclear how (a) this research applies to middle-aged adults (such as those in Study 1), (b) this might extend to a masked dot-probe paradigm, or (c) the effect of trauma impacts SST. Sixth, the majority (94%) of Study 1 participants had a comorbid Substance Use Disorder (SUD) diagnosis, where only a portion (35%) of Study 2 did.…”
Section: Discussionmentioning
confidence: 99%
“…Two experiments (Humpreys et al, 2010; Kim et al, 2013) using paired-pictures reported greater fixations to negative than neutral images, which translated into enhanced memory for negative over neutral items at recall. One experiment (Chang & Choi, 2014) reported that gaze duration predicted memory for emotional narratives but not for emotional images, while another study (Bi & Han, 2015) found that greater fixation time toward negative than positive and neutral stimuli predicted memory performance for negative stimuli. Of the 15 experiments, one (Ziaei et al, 2015) measured pupillary responses, and reported larger pupil sizes for positive targets presented with negative distractors relative to neutral distractors, which translated into greater memory for positive items.…”
Section: Resultsmentioning
confidence: 99%